منهج التعامل مع المسيء إلى الرسول صلى الله عليه وسلم في ضوء السنة النبوية: دراسة تحليلية - إسلام، محمد سيف (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
Treating the Prophet improperly — despite it being an old topic — had emerged nowadays in a new guise. Muslims had been responding to this provocation, sometimes in accordance with the teaching of Islam itself and sometimes by breaking its rules. This study aims to study the approaches of the Prophet himself and his Ummah (Nation) in dealing with this issue. The study is divided into a brief introduction and several sub-topics that represent the different approached of the Prophet (SAW) and his Ummah (Nation) in dealing with those who treated Prophet (SAW) improperly. The study made use of the library research method with content analysis. Among the most important conclusions are that most of the methods in dealing with those who badly treated the Prophet (SAW) are based on wisdom, good advice, addressing abusers with soft behaviour and characteristic, meeting, discussing and educating them about the biography of the Prophet (SAW). These are the most important outcomes from this thesis. The researcher hopes that this research would contribute to a positive solution to respond to conflicts when the Prophet (SAW) is placed in such derogatory situations.